Ownership, Audit Committee, Trigger of Fraud, and Manipulation of Financial Statements - Trisnanda, Rizky Azzahra Nur; Surifah, Surifah (Journal of International Conference Proceedings, 2023)
Research on financial statements manipulation (MFS) in the construction industry is interesting because this industry is one of the industries that practice fraud the most, reaching 16%. In addition, this research is important because MFS continues to occur with increasing amounts, and has a high risk of loss. This research objectives is to prove the impact of ownership, audit committees, and triggers of fraud on (MFS). The results show that foreign institutional ownership, audit committees, opportunity, and arrogance have a significant negative effect on MFS. The higher the level of ownership of foreign institutions, audit committees, opportunity, and arrogance, the more manipulation of will be prevented. Individual ownership and pressure have a significant positive impact on MFS. The higher the pressure and level of individual shareholders, the greater the potential for MFS. There are several proxies for detecting MFS. This research uses the discretionary accrual Jones modified earnings management proxy. Other research can use other proxies such as MFS through real activities. Further research will be more interesting if it compares the effect of ownership, audit committees, and MFS in the construction industry of ASEAN countries.